A radiation energy-saving coating with high entropy ceramics as functional pigments

By using high-entropy ceramic powder A2B2O7 and other functional materials, combined with composite high-temperature binders and additives, a radiation energy-saving coating with excellent infrared emissivity and low thermal conductivity is prepared, which solves the problem of the infrared emission band of existing coatings at high temperatures. Narrow range of problems, achieving efficient thermal energy radiation and low thermal conductivity isolation.

CN118146661BActive Publication Date: 2025-01-21LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410279393.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-12
Publication Date
2025-01-21
Estimated Expiration
2044-03-12

AI Technical Summary

Technical Problem

The existing infrared radiation coatings have narrow infrared emission band ranges at high temperatures, and their thermal conductivity and infrared emissivity are not excellent enough, making them difficult to be suitable for high-temperature environments.

Method used

High-entropy ceramic powder A2B2O7 is used as a functional pigment, combined with chromium oxide, zirconia, brown corundum, silicon carbide and other materials, and through the combination of composite high-temperature binders and additives, a product with excellent infrared emissivity and low thermal conductivity is prepared Radiant energy-saving paint.

Benefits of technology

The infrared emissivity in the 1~20μm band exceeds 0.94, and the thermal conductivity is lower than 0.8 W·(m·k)-1. It is suitable for high temperature environments of 1200~1800℃, improving thermal efficiency and high temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118146661B_ABST
    Figure CN118146661B_ABST
Patent Text Reader

Abstract

The present invention relates to a radiation energy-saving coating with high entropy ceramic as functional pigment, and the radiation energy-saving coating is composed of the following raw materials in parts by weight: 10-20 parts of high entropy ceramic powder, 0-10 parts of chromium oxide, 5-10 parts of zirconium oxide, 5-10 parts of brown corundum, 3-5 parts of silicon carbide, 3-5 parts of cordierite, 3-5 parts of mullite, 3-5 parts of bentonite, 2-5 parts of cerium oxide, 2-5 parts of yttrium oxide, 1-3 parts of metal powder, 1-3 parts of defoamer, 1-3 parts of leveling agent, 1-3 parts of wetting dispersant, 1-3 parts of anti-settling agent, 20-30 parts of composite high-temperature binder, and 15-25 parts of deionized water. The high entropy ceramic powder has a defective fluorite or pyrochlore structure, belongs to a cubic facet system, Fm-3m space group or Fd-3m space group, and has a chemical formula of A2B2O7, wherein the A position is La, Pr, Gd, Ca, Cu, Fe 、 The B position is two of Ce, Zr, Ti, Cr and Mn. The invention has high temperature thermal stability, low infrared attenuation rate after long-term use and a thermal expansion coefficient matching the substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of radiation energy-saving technology, and in particular to a radiation energy-saving coating using high-entropy ceramics as functional pigments. Background Art

[0002] Industrial kilns, as energy conversion equipment, have problems such as high energy consumption, low thermal efficiency, and serious air pollution. High-temperature infrared radiation coatings can effectively improve heat exchange in the furnace, increase the temperature field intensity and uniformity in the furnace, and make coal burn more fully, thereby achieving the effect of improving thermal efficiency, reducing coal consumption, and saving energy and reducing carbon. Heat transfer theory believes that the greater the blackness of an object, the higher its absorptivity and emissivity. When coal burns in the furnace, heat energy is radiated to the water-cooled wall in the form of electromagnetic waves. The water-cooled wall absorbs part of the electromagnetic waves and converts them into thermal energy, thereby heating up the surface of the furnace wall and transferring heat to the inside. At the same time, part of the electromagnetic waves are emitted back to the furnace, thereby increasing the temperature in the furnace.

[0003] CN 102702808 B discloses an infrared radiation coating capable of forming a low thermal conductivity coating, the coating has excellent infrared radiation performance and low thermal conductivity, and can be firmly combined with a refractory material matrix, and does not crack or fall off during long-term use at high temperatures of 500-1300°C, and has excellent corrosion resistance and thermal shock resistance. However, the preparation process of the spinel-silicate multiphase composite powder, which mainly plays the role of infrared radiation performance of the coating, is complicated, the embryo needs to be calcined in stages, and the calcination temperature requirements are strict; and the porous structure formed by the drying and curing of the coating is not conducive to the wear resistance of the coating, and the unstable porous structure will cause serious attenuation of thermal conductivity and infrared emissivity.

[0004] CN 112723884 A discloses a ceramic material with both low thermal conductivity and high infrared emissivity, a ceramic coating and a preparation method thereof. The ceramic material is synthesized from HfO2 and Sm2O3 by high-temperature solid-phase reaction, and has the characteristics of low thermal conductivity and high infrared emissivity. The coating is prepared by plasma spraying technology, and the emissivity in the mid-infrared band of 8-14μm in the range of room temperature to 600℃ is 0.90-0.95. However, the infrared emission band of the ceramic material is narrow, and it is not suitable for use in an environment with a temperature greater than 1000℃ (when the temperature is higher than 1000℃, the corresponding band of the radiation energy is mainly concentrated in the range of 1-5μm).

[0005] CN 114956802 A discloses a low thermal conductivity infrared emission material and its preparation method and application, which uses MgO, Co3O4, NiO, CuO, ZnO, A12O3, and Cr2O3 as raw materials, and is pressed into shape after ball milling, drying, screening, and finally sintered at high temperature to obtain a spinel high entropy material, and the infrared emissivity in the 3-5μm band is 0.86-0.98. However, the infrared emission band range of the material is relatively narrow, which is not conducive to the use of infrared emission performance in the mid-infrared band. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a radiation energy-saving coating with good performance and high entropy ceramics as functional pigments.

[0007] In order to solve the above problems, the present invention discloses a radiation energy-saving coating with high entropy ceramic as functional pigment, characterized in that the radiation energy-saving coating is composed of the following raw materials in parts by weight: 10-20 parts of high entropy ceramic powder, 0-10 parts of chromium oxide, 5-10 parts of zirconium oxide, 5-10 parts of brown corundum, 3-5 parts of silicon carbide, 3-5 parts of cordierite, 3-5 parts of mullite, 3-5 parts of bentonite, 2-5 parts of cerium oxide, 2-5 parts of yttrium oxide, and metal 1-3 parts of powder, 1-3 parts of defoaming agent, 1-3 parts of leveling agent, 1-3 parts of wetting dispersant, 1-3 parts of anti-settling agent, 20-30 parts of composite high-temperature binder, and 15-25 parts of deionized water; the high-entropy ceramic powder has a defective fluorite or pyrochlore structure, belongs to a cubic facet system, a Fm-3m space group or a Fd-3m space group, and its chemical formula is A2B2O7, wherein the A position is La, Pr, Gd, Ca, Cu, Fe 、 The B position contains three of Ni and Co, and the ratio of each element is equimolar or nearly equimolar, and the B position contains two of Ce, Zr, Ti, Cr and Mn, and the molar mass ratio of the two elements is 1:1.

[0008] The infrared emissivity of the radiation energy-saving coating in the 1-20 μm band is greater than 0.94, and the thermal conductivity is less than 0.8 W·(m·k) -1 , the operating temperature is 1200~1800℃.

[0009] The particle sizes of the chromium oxide, silicon carbide, cerium oxide and yttrium oxide are all 200-300 nm; the particle sizes of the zirconium oxide and brown corundum are all 300-500 nm; and the particle sizes of the cordierite and mullite are all 100-400 meshes.

[0010] The metal powder is one or two of metal molybdenum, metal copper and metal chromium, and its particle size is less than 1 μm.

[0011] The composite high-temperature adhesive is a composite adhesive obtained by uniformly mixing chromium aluminum phosphate, modified aluminum dihydrogen phosphate, and silica sol in a mass ratio of 1: (0.6-0.8): (0.2-0.4).

[0012] The defoaming agent is one or two of TEGO 901W polyether siloxane defoaming agent, TEGO 8030 silicone water-based defoaming agent, and EFKA 2720 unsaturated polyester defoaming agent; the leveling agent is one or two of TEGO Glide450 silicone leveling agent, EFKA 3777 polyurethane leveling agent, and EFKA 3034 leveling agent; the wetting and dispersing agent is one or two of TEGO 755W, TEGO 662 C, and EFKA 5065.

[0013] The anti-settling agent is DH-6930S.

[0014] The method for preparing the radiation energy-saving coating using high entropy ceramic as a functional pigment as described above comprises the following steps:

[0015] Step 1: Add high entropy ceramic powder to the composite high temperature binder, mechanically stir for 10 to 15 minutes, and after stirring evenly, add chromium oxide, zirconium oxide, brown corundum, silicon carbide, cordierite, mullite, bentonite, cerium oxide, yttrium oxide, and metal powder in sequence, and mechanically stir for 30 to 60 minutes to obtain a mixture A;

[0016] Step 2: Add deionized water to the mixture A and stir mechanically for 5 to 10 minutes; then add a defoamer, a leveling agent, a wetting and dispersing agent, and an anti-settling agent in sequence and stir mechanically for 30 to 60 minutes to obtain a mixture B;

[0017] Step 3: Transfer the mixture B to a planetary ball mill, wherein the ball milling medium is zirconia balls, the ball-to-material mass ratio is 2:1, the ball milling speed is 200-400 r / min, and the ball milling time is 2-4 hours, to obtain a radiation energy-saving coating.

[0018] The method for using the radiation energy-saving coating with high-entropy ceramics as functional pigments as described above is characterized in that the radiation energy-saving coating is applied to any substrate including the lining of the high-temperature kiln wall, heat storage balls, refractory bricks, and refractory fibers by any one of spraying, roller coating, and dipping.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. The high entropy ceramic powder A2B2O7 in the present invention is a type of structural ceramic material with a large adjustable component space and strong structural inclusiveness. The A and B sites can be chemically replaced by a variety of rare earth or transition metal elements at the same time. The multiple principal element structure forms an intermediate band near the Fermi level, effectively reducing the band gap. In addition, due to the disorder of the elements and the differences in radius and mass, the crystal structure of the material presents severe lattice distortion. In order to balance the electrical neutrality, the metal elements will undergo valence state transformation and produce small polarons, which are all conducive to improving the infrared emissivity of the material in the 1~20μm band, especially in the mid-infrared band (1.4~3μm).

[0021] 2. The present invention uses A2B2O7 type high entropy ceramics as the main infrared emitting powder material, and prepares radiation energy-saving coatings by adding functional fillers, high-temperature binders, additives, etc. It has the advantages of simple preparation technology, strong repeatability, high production efficiency, and applicability to automated operations.

[0022] 3. The radiation energy-saving coating of the present invention has a low thermal conductivity. Due to the mutual doping of elements with different atomic masses and atomic radii in the lattice of the high-entropy ceramic filler, the nonlinear vibration of the crystal increases, thereby reducing the mean free path of the phonons, further aggravating the scattering effect between phonons, resulting in low thermal conductivity. According to the test standard ASTME1461-13 (2022) "Standard Test Method for Thermal Diffusivity by the Flash Method", the radiation energy-saving coating is sprayed on the surface of the refractory brick, and the thermal conductivity of the coating at 800°C is 0.68 W·(m·K) -1 .

[0023] 4. The radiation energy-saving coating of the present invention has high infrared emissivity and low thermal conductivity in the 1-20 μm band. It combines high infrared emissivity with low thermal conductivity, and can both emit radiant heat energy through high emission and isolate heat energy through low thermal conductivity. When the heat flux density range is certain, the higher the emissivity of the furnace surface, the more effectively it can absorb electromagnetic waves and convert them into heat energy. At the same time, part of the electromagnetic waves are emitted back to the furnace, improving the heat exchange in the furnace, increasing the temperature field intensity and uniformity in the furnace, and making the coal burn more fully, thereby achieving the effect of improving thermal efficiency and energy saving.

[0024] 5. The use temperature of the radiation energy-saving coating of the present invention is 1200~1800℃. The composite high-temperature adhesive used is a combination of chromium aluminum phosphate, modified aluminum dihydrogen phosphate and silica sol. The bonding strength of aluminum dihydrogen phosphate is modified by mullite fiber; chromium aluminum phosphate is introduced into 3+The disadvantage of poor thermal stability of aluminum phosphate is made up, and silica sol improves the strength. Therefore, the composite high-temperature binder used in the present invention has the characteristics of stronger chemical bonding, high temperature resistance, thermal shock resistance, high temperature air flow erosion resistance, and good high temperature stability.

[0025] 6. The radiation energy-saving coating of the present invention has excellent thermal stability. The radiation energy-saving coating is sprayed on the surface of the refractory brick and heat-treated for 1000 hours at 1500℃. The coating surface is smooth, dense, without blistering, cracking and other phenomena, and the infrared attenuation rate is less than 1%. This is because high-entropy ceramics have a unique high-entropy effect. At high temperatures, the change in entropy terms (T·ΔS) is much greater than the change in enthalpy terms (ΔH), resulting in the Gibbs free energy (ΔG=ΔH- T·ΔS) being less than zero, and the system spontaneously tends to be stable. The high-entropy ceramics maintain the original structure, phase and infrared radiation performance unchanged. Combined with the excellent high-temperature resistance of the composite high-temperature binder, the radiation energy-saving coating is endowed with excellent thermal stability and extremely low infrared attenuation rate.

[0026] 7. The radiation energy-saving coating of the present invention has a thermal expansion coefficient that matches that of the refractory material. -6 / K), silicon carbide (3.7×10 -6 / K), mullite (5.0×10 -6 / K) and other functional fillers with low thermal expansion coefficients, and the thermal expansion properties of the radiation energy-saving coatings are adjusted by adjusting the ratio of the components in the coatings. According to the GB / T 7320-2018 "Coating Thermal Expansion Coefficient" test standard, the obtained radiation energy-saving coatings are sprayed on refractory bricks, and the linear thermal expansion coefficient within 25~800℃ is (5.38~6.25)×10 -6 / ℃, which can effectively reduce the stress caused by thermal shock during thermal cycle testing.

[0027] 8. The radiation energy-saving coating of the present invention has excellent resistance to molten salt corrosion. Functional fillers of different particle sizes are selected, which can be filled with high-temperature binders during the curing process to form a continuous and dense ceramic glaze layer with a smooth and dense surface, which can prevent the external high-temperature atmosphere and corrosive substances from diffusing into the interior of the substrate, and play an anti-corrosion protection role.

[0028] 9. The present invention has high-temperature thermal stability, a low infrared attenuation rate after long-term use, and a thermal expansion coefficient that matches the substrate. It has broad application prospects in the fields of heat insulation and heat preservation of industrial kilns, spacecraft, supersonic aircraft, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0030] Figure 1This is the infrared emission spectrum of the radiation energy-saving coating prepared in Example 1 of the present invention.

[0031] Figure 2 This is a surface image of the coating after the radiation energy-saving coating prepared in Example 2 of the present invention is sprayed on an alumina crucible plate and subjected to high-temperature molten salt corrosion.

[0032] Figure 3 The radiation energy-saving coating prepared in Example 2 of the present invention was sprayed on an alumina crucible to test its wear resistance. The left picture is a photo of the wear test process; the right picture is the morphology of the coating on the crucible surface after the wear test.

[0033] Figure 4 This is the coating appearance picture of the radiation energy-saving coating prepared in Example 3 of the present invention after being sprayed on refractory bricks and subjected to high temperature resistance test.

[0034] Figure 5 This is a thermal expansion coefficient diagram of the radiation energy-saving coating prepared in Example 4 of the present invention sprayed on refractory bricks. DETAILED DESCRIPTION

[0035] A radiation energy-saving coating with high entropy ceramic as functional pigment, the radiation energy-saving coating is composed of the following raw materials in parts by weight (g): 10-20 parts of high entropy ceramic powder, 0-10 parts of chromium oxide, 5-10 parts of zirconium oxide, 5-10 parts of brown corundum, 3-5 parts of silicon carbide, 3-5 parts of cordierite, 3-5 parts of mullite, 3-5 parts of bentonite, 2-5 parts of cerium oxide, 2-5 parts of yttrium oxide, 1-3 parts of metal powder, 1-3 parts of defoaming agent, 1-3 parts of leveling agent, 1-3 parts of wetting dispersant, 1-3 parts of anti-settling agent, 20-30 parts of composite high-temperature binder, and 15-25 parts of deionized water. The high entropy ceramic powder has a defective fluorite or pyrochlore structure, belongs to a cubic facet system, Fm-3m space group or Fd-3m space group, and has a chemical formula of A2B2O7, wherein the A position is La, Pr, Gd, Ca, Cu, Fe 、 The B position contains three of Ni and Co, and the ratio of each element is equimolar or nearly equimolar, and the B position contains two of Ce, Zr, Ti, Cr and Mn, and the molar mass ratio of the two elements is 1:1.

[0036] The infrared emissivity of the radiation energy-saving coating in the 1~20μm band is greater than 0.94, and the thermal conductivity is less than 0.8 W·(m·k) -1 , the operating temperature is 1200~1800℃.

[0037] Wherein: High entropy ceramic powder is prepared by the following method: AO with a molar ratio of metal elements of 1:1 x Powder and BO y Powder as raw material, AO x La2O3, Pr6O 11、Gd2O3、CaO、CuO、Fe2O 3、 Three of NiO and CoO powders, and the ratio of the selected elements is equimolar or nearly equimolar, BO y The raw materials are two of CeO2, ZrO2, TiO2, Cr2O3, and MnO2 powders, and the content of the two elements is 1:1. The raw materials are ball-milled and mixed in a planetary ball mill, the ball milling medium is zirconia ball, the ball milling speed is 200~400 r / min, the ball milling time is 12~24 hours, and the mass ratio of ball material to water (g / g) is 3:1:2. Then, the mixture powder is obtained by drying at 80~100℃ for 12~24 hours and grinding. The mixture powder is calcined at high temperature in an air atmosphere, the calcination temperature is 1200~1500℃, the heating rate is 3~5℃ / min, and the calcination time is 6~8 hours. After calcination, high entropy ceramic powder material with a particle size of 500~1000nm is obtained by cooling, grinding, and sieving.

[0038] The particle sizes of chromium oxide, silicon carbide, cerium oxide and yttrium oxide are all 200-300nm; the particle sizes of zirconium oxide and brown corundum are all 300-500nm; the particle sizes of cordierite and mullite are all 100-400 meshes.

[0039] The metal powder is one or two of metal molybdenum, metal copper and metal chromium, and its particle size is less than 1 μm.

[0040] The composite high-temperature binder refers to a composite binder obtained by uniformly mixing chromium aluminum phosphate, modified aluminum dihydrogen phosphate, and silica sol in a mass ratio (g / g) of 1: (0.6~0.8): (0.2~0.4).

[0041] The defoaming agent is one or two of TEGO 901W polyether siloxane defoaming agent, TEGO 8030 silicone water-based defoaming agent, and EFKA 2720 unsaturated polyester defoaming agent; the leveling agent is one or two of TEGO Glide 450 silicone leveling agent, EFKA 3777 polyurethane leveling agent, and EFKA 3034 leveling agent; the wetting and dispersing agent is one or two of TEGO 755W, TEGO 662 C, and EFKA 5065.

[0042] The anti-settling agent is DH-6930S produced by Suzhou Qingtian New Materials Co., Ltd.

[0043] A method for preparing a radiation energy-saving coating using high-entropy ceramics as functional pigments comprises the following steps:

[0044] Step 1: Add high entropy ceramic powder to the composite high temperature binder, mechanically stir for 10 to 15 minutes, and after stirring evenly, add chromium oxide, zirconium oxide, brown corundum, silicon carbide, cordierite, mullite, bentonite, cerium oxide, yttrium oxide, and metal powder in sequence, and mechanically stir for 30 to 60 minutes to obtain a mixture A;

[0045] Step 2: Add deionized water to mixture A and stir mechanically for 5 to 10 minutes; then add defoamer, leveling agent, wetting dispersant, and anti-settling agent in sequence and stir mechanically for 30 to 60 minutes to obtain mixture B;

[0046] Step 3: Transfer the mixture B to a planetary ball mill, the ball milling medium is zirconia balls, the ball-to-material mass ratio (g / g) is 2:1, the ball milling speed is 200-400 r / min, and the ball milling time is 2-4 hours to obtain the radiation energy-saving coating.

[0047] A method for using a radiation energy-saving coating with high-entropy ceramics as functional pigments: applying the radiation energy-saving coating to any substrate of a high-temperature kiln wall lining, heat storage balls, refractory bricks, and refractory fibers by any of spraying, roller coating, and dipping.

[0048] Example 1

[0049] A method for preparing a radiation energy-saving coating using high-entropy ceramics as functional pigments comprises the following steps:

[0050] Step 1: 10g high entropy ceramic powder (La 0.33 Pr 0.34 Co 0.34 )2(Ce 0.5 Zr 0.5 )2O7 is added to 20g of a composite high-temperature binder (10g of chromium aluminum phosphate, 6g of modified aluminum dihydrogen phosphate, and 4g of silica sol), and mechanically stirred for 10 minutes. After being uniformly stirred, 10g of chromium oxide, 6g of zirconium oxide, 5g of brown corundum, 4g of silicon carbide, 5g of cordierite, 5g of mullite, 3g of bentonite, 2g of cerium oxide, 5g of yttrium oxide, and 3g of metal molybdenum are added in sequence and mechanically stirred for 30 minutes to obtain a mixture A;

[0051] Step 2: Add 15 g of deionized water to mixture A and stir mechanically for 5 minutes; then add 2 g of defoamer (TEGO 901W, TEGO 8030), 1 g of leveling agent (Glide 450), 3 g of wetting and dispersing agent (TEGO 755W, TEGO 662 C), and 1 g of anti-settling agent (DH-6930S) in sequence, and stir mechanically for 30 minutes to obtain mixture B;

[0052] Step 3: Transfer the mixture B to a planetary ball mill, the ball milling medium is zirconia balls, the ball-to-material mass ratio (g / g) is 2:1, 200 r / min, and the ball milling time is 4 hours to obtain the radiation energy-saving coating.

[0053] According to GB / T 4653-1984 "Coating Infrared Radiation Rate" standard, the obtained radiation energy-saving coating was tested, and the results are as follows: Figure 1 As shown, the normal infrared emissivity of the coating in the range of 1 to 20 μm is 0.948.

[0054] Example 2

[0055] A method for preparing a radiation energy-saving coating using high-entropy ceramics as functional pigments comprises the following steps:

[0056] Step 1: 13g high entropy ceramic powder (La 0.33 G 0.34 Fe 0.34 )2(Ti 0.5 Mn 0.5 )2O7 is added to 25g of a composite high-temperature binder (12.5g of chromium aluminum phosphate, 10g of modified aluminum dihydrogen phosphate, and 2.5g of silica sol), and mechanically stirred for 13 minutes. After being stirred evenly, 6g of chromium oxide, 5g of zirconium oxide, 6g of brown corundum, 3g of silicon carbide, 3g of cordierite, 3g of mullite, 3g of bentonite, 5g of cerium oxide, 2g of yttrium oxide, and 1g of metallic copper are added in sequence, and mechanically stirred for 45 minutes to obtain a mixture A;

[0057] Step 2: Add 20 g of deionized water to mixture A and stir mechanically for 10 minutes; then add 1 g of defoamer (EFKA 2720), 1 g of leveling agent (EFKA 3777), 1 g of wetting and dispersing agent (TEGO 755W), and 2 g of anti-settling agent (DH-6930S) in sequence, and stir mechanically for 60 minutes to obtain mixture B;

[0058] Step 3: Transfer the mixture B to a planetary ball mill, the ball milling medium is zirconia balls, the ball-to-material mass ratio (g / g) is 2:1, the ball milling speed is 400 r / min, and the ball milling time is 2 hours to obtain the radiation energy-saving coating.

[0059] The obtained radiation energy-saving coating was sprayed on an alumina crucible, and a saturated solution of Na2SO4 and K2SO4 with a mass ratio (g / g) of 19:1 was prepared. The saturated salt solution was brushed on the surface of the sample to make the salt film mass 10-12 mg / cm 2 After that, the sample was placed in a resistance furnace and heated to 700℃ for 240 hours of corrosion test. Figure 2 As shown, the obtained coating surface is smooth and dense, without blistering, cracking and the like.

[0060] According to the GB / T 23988-2009 "Determination of Wear Resistance of Coatings by Falling Sand Method" test standard, the obtained radiation energy-saving coating was sprayed on an alumina crucible to test the wear resistance, and the result was 5L / μm. Figure 3 shown.

[0061] Example 3

[0062] A method for preparing a radiation energy-saving coating using high-entropy ceramics as functional pigments comprises the following steps:

[0063] Step 1: Mix 20g of high entropy ceramic powder (La 0.33 Cu 0.34 Ni 0.34 )2(Ce 0.5 Cr 0.5 )2O7 is added to 20g of a composite high-temperature binder (10g of chromium aluminum phosphate, 7g of modified aluminum dihydrogen phosphate, and 3g of silica sol), and mechanically stirred for 10 minutes. After being stirred evenly, 10g of zirconium oxide, 5g of brown corundum, 5g of silicon carbide, 3g of cordierite, 3g of mullite, 5g of bentonite, 3g of cerium oxide, 2g of yttrium oxide, and 1g of metallic chromium are added in sequence, and mechanically stirred for 60 minutes to obtain a mixture A;

[0064] Step 2: Add 15 g of deionized water to mixture A and stir mechanically for 8 minutes; then add 3 g of defoamer (TEGO 8030, EFKA 2720), 2 g of leveling agent (EFKA 3777, EFKA 3034), 2 g of wetting and dispersing agent (TEGO 755W, TEGO 662 C), and 1 g of anti-settling agent (DH-6930S) in sequence, and stir mechanically for 45 minutes to obtain mixture B;

[0065] Step 3: Transfer the mixture B to a planetary ball mill, the ball milling medium is zirconia balls, the ball-to-material mass ratio (g / g) is 2:1, the ball milling speed is 300 r / min, and the ball milling time is 4 hours to obtain the radiation energy-saving coating.

[0066] According to the test standard GB / T 1735-2009 "Determination of Heat Resistance of Paints and Varnishes", the obtained radiation energy-saving coating was sprayed on refractory bricks and placed in the air atmosphere of a box furnace. After a 1000-hour thermal stability test at 1500°C, the coating surface was smooth, dense, without blistering, cracking, etc. Figure 4 As shown, the infrared attenuation rate is less than 1%, which indicates that the radiation energy-saving coating of the present invention has excellent high temperature resistance.

[0067] Example 4

[0068] A method for preparing a radiation energy-saving coating using high-entropy ceramics as functional pigments comprises the following steps:

[0069] Step 1: 10g high entropy ceramic powder (Pr 0.33 G 0.34 Cu 0.34 )2(Ce 0.5 Mn 0.5 )2O7 is added to 30g of a composite high-temperature binder (15g of aluminum chromium phosphate, 12g of modified aluminum dihydrogen phosphate, and 3g of silica sol), and mechanically stirred for 15 minutes. After being stirred evenly, 5g of zirconium oxide, 10g of brown corundum, 3g of silicon carbide, 4g of cordierite, 4g of mullite, 4g of bentonite, 2g of cerium oxide, 3g of yttrium oxide, and 2g of metal powder (1g of molybdenum and 1g of copper) are added in sequence, and mechanically stirred for 60 minutes to obtain a mixture A;

[0070] Step 2: Add 15 g of deionized water to mixture A and stir mechanically for 5 minutes; then add 1 g of defoamer (EFKA 2720), 3 g of leveling agent (Glide 450, EFKA 3777), 1 g of wetting and dispersing agent (TEGO 662 C), and 3 g of anti-settling agent (DH-6930S) in sequence, and stir mechanically for 45 minutes to obtain mixture B;

[0071] Step 3: Transfer the mixture B to a planetary ball mill, the ball milling medium is zirconia balls, the ball-to-material mass ratio (g / g) is 2:1, the ball milling speed is 300 r / min, and the ball milling time is 4 hours to obtain the radiation energy-saving coating.

[0072] According to the GB / T 7320-2018 "Coating Thermal Expansion Coefficient" test standard, the obtained radiation energy-saving coating was sprayed on the refractory bricks. Its linear thermal expansion coefficient within 25~800℃ is (5.38~6.25)×10 -6 / ℃, such as Figure 5 As shown, it has a thermal expansion coefficient that matches that of the substrate, and can effectively reduce the stress caused by thermal shock during thermal cycle testing.

[0073] According to the test standard GB / T 30873-2014 "Test Method for Thermal Shock Resistance of Refractory Materials", the radiation energy-saving coating was sprayed on the refractory bricks. After 60 thermal shock resistance tests at 1000°C, the coating surface was smooth, dense, and free of blistering, cracking, etc. This shows that the radiation energy-saving coating of the present invention has good thermal shock resistance.

[0074] Example 5

[0075] A method for preparing a radiation energy-saving coating using high-entropy ceramics as functional pigments comprises the following steps:

[0076] Step 1: 10g high entropy ceramic powder (Pr 0.33 G 0.34 Ni 0.34 )2(Ce 0.5 Ti 0.5 )2O7 is added to 20g of a composite high-temperature binder (10g of chromium aluminum phosphate, 6g of modified aluminum dihydrogen phosphate, and 4g of silica sol), and mechanically stirred for 13 minutes. After being uniformly stirred, 5g of chromium oxide, 5g of zirconium oxide, 5g of brown corundum, 3g of silicon carbide, 4g of cordierite, 4g of mullite, 5g of bentonite, 2g of cerium oxide, 3g of yttrium oxide, and 2g of metal powder (1g of chromium and 1g of copper) are added in sequence, and mechanically stirred for 50 minutes to obtain a mixture A;

[0077] Step 2: Add 20 g of deionized water to mixture A and stir mechanically for 5 minutes; then add 1 g of defoamer (TEGO 8030, EFKA 2720), 3 g of leveling agent (Glide 450, EFKA 3034), 1 g of wetting and dispersing agent (EFKA 5065), and 3 g of anti-settling agent (DH-6930S) in sequence, stir mechanically for 30 minutes, and obtain mixture B;

[0078] Step 3: Transfer the mixture B to a planetary ball mill, the ball milling medium is zirconia balls, the ball-to-material mass ratio (g / g) is 2:1, the ball milling speed is 300 r / min, and the ball milling time is 2 hours to obtain the radiation energy-saving coating.

[0079] The above is only an explanation of the best embodiment of the present invention, which should not be construed as a limitation on the claims. The present invention is not limited to the above embodiments. All changes made within the scope of protection of the independent claims of the present invention are within the scope of protection of the present invention.

Claims

1. A radiation energy-saving coating with high entropy ceramics as functional pigments, characterized in that: The radiation energy-saving coating is composed of the following raw materials in parts by weight: 10-20 parts of high-entropy ceramic powder, 0-10 parts of chromium oxide, 5-10 parts of zirconium oxide, 5-10 parts of brown corundum, 3-5 parts of silicon carbide, 3-5 parts of cordierite, 3-5 parts of mullite, 3-5 parts of bentonite, 2-5 parts of cerium oxide, 2-5 parts of yttrium oxide, 1-3 parts of metal powder, 1-3 parts of defoaming agent, 1-3 parts of leveling agent, 1-3 parts of wetting dispersant, 1-3 parts of anti-settling agent, 20-30 parts of composite high-temperature binder, and 15-25 parts of deionized water; the high-entropy ceramic powder has a defective fluorite or pyrochlore structure, belongs to a cubic facet system, Fm-3m space group or Fd-3m space group, and has a chemical formula of A2B2O7, wherein the A position is La, Pr, Gd, Ca, Cu, Fe 、 The invention relates to a composite material comprising three kinds of Ni and Co, and the ratio of each element is equimolar or nearly equimolar, two kinds of Ce, Zr, Ti, Cr and Mn are in the B position, and the molar mass ratio of the two elements is 1:1; the particle sizes of the chromium oxide, silicon carbide, cerium oxide and yttrium oxide are 200-300nm; the particle sizes of the zirconium oxide and brown corundum are 300-500nm; the particle sizes of the cordierite and mullite are 100-400 mesh; the composite high-temperature binder refers to a composite binder obtained by uniformly mixing aluminum chromium phosphate, modified aluminum dihydrogen phosphate and silica sol in a mass ratio of 1: (0.6-0.8): (0.2-0.4); the defoamer is one or two of TEGO 901W polyether siloxane defoamer, TEGO 8030 silicone water-based defoamer and EFKA 2720 unsaturated polyester defoamer; the leveling agent is Glide One or two of EFKA 450 organic silicone leveling agent, EFKA 3777 polyurethane leveling agent, and EFKA 3034 leveling agent; the wetting and dispersing agent is one or two of TEGO 755W, TEGO 662 C, and EFKA 5065.

2. The radiation energy-saving coating with high entropy ceramic as functional pigment according to claim 1, characterized in that: The infrared emissivity of the radiation energy-saving coating in the 1-20 μm band is greater than 0.94, and the thermal conductivity is less than 0.8 W·(m·k) -1 , the operating temperature is 1200~1800℃.

3. The radiation energy-saving coating with high entropy ceramic as functional pigment according to claim 1, characterized in that: The metal powder is one or two of metal molybdenum, metal copper and metal chromium, and its particle size is less than 1 μm.

4. The radiation energy-saving coating with high entropy ceramic as functional pigment according to claim 1, characterized in that: The anti-settling agent is DH-6930S.

5. The method for preparing a radiation energy-saving coating with high entropy ceramic as a functional pigment as claimed in claim 1, comprising the following steps: Step 1: Add high entropy ceramic powder to the composite high temperature binder, mechanically stir for 10 to 15 minutes, and after stirring evenly, add chromium oxide, zirconium oxide, brown corundum, silicon carbide, cordierite, mullite, bentonite, cerium oxide, yttrium oxide, and metal powder in sequence, and mechanically stir for 30 to 60 minutes to obtain a mixture A; Step 2: Add deionized water to the mixture A and stir mechanically for 5 to 10 minutes; then add a defoamer, a leveling agent, a wetting and dispersing agent, and an anti-settling agent in sequence and stir mechanically for 30 to 60 minutes to obtain a mixture B; Step 3: Transfer the mixture B to a planetary ball mill, wherein the ball milling medium is zirconia balls, the ball-to-material mass ratio is 2:1, the ball milling speed is 200-400 r / min, and the ball milling time is 2-4 hours, to obtain a radiation energy-saving coating.

6. The method for using the radiation energy-saving coating with high entropy ceramic as functional pigment according to claim 1, characterized in that: The radiation energy-saving coating is applied to any substrate including the inner lining of the high-temperature kiln wall, heat storage balls, refractory bricks and refractory fibers by any method including spraying, roller coating and dipping.

Citation Information

Patent Citations

  • Infrared radiation coating capable of forming coating with low conductivity factor

    CN102702808B

  • Ceramic material and ceramic coating with low thermal conductivity and high infrared emissivity, and preparation methods thereof

    CN112723884A

  • High-entropy ceramic thermal barrier coating

    CN115043659A

  • High-temperature and high-radiance protective coating for coal-fired boiler and preparation method thereof

    CN115724658A